(untitled) (American Journal of Business Management, Economics and Banking, 2024)
The second important source of filling the budget is customs duties, and in the integration of the country’s economy into the world economy, it is one of the most urgent issues to optimize the use of customs duties and benefits based on the requirements of the market situation, taking into account the experiences of foreign countries in this direction. Based on the laws and regulatory documents adopted for the purpose of all-round support for enterprises producing competitive ready-made goods that substitute for imports, modernization of the economy, stimulation of technical and technological equipment, and improvement of the investment environment, a number of benefits have been granted to the participants of foreign economic activity.